Atrial fibrillation and pneumothorax after transthoracic needle lung biopsy - Liu, Alexander (BMJ Publishing Group, 2012)
An obese 65-year-old male smoker with chronic obstructive pulmonary disease developed an iatrogenic pneumothorax with pulmonary haemorrhage during an elective transthoracic needle biopsy of a pulmonary lesion. Successful re-inflation was achieved with a chest drain which was then removed before transfer to the medical ward. He later developed persistent atrial fibrillation with breathlessness and haemoptysis. He was treated empirically for a pulmonary embolus, which was subsequently ruled out with CT pulmonary angiogram. Serial chest radiographs demonstrated recurrence of his pneumothorax and a chest drain was re-inserted. His atrial fibrillation was erroneously managed as supraventricular tachycardia, which was resistant to vagal manoeuvres and adenosine but later responded to intravenous amiodarone before a further relapse. Upon successful management of the pneumothorax, his atrial fibrillation terminated. This case highlighted the persistent and serious nature of complications posttransthoracic needle biopsy.